Advances in somatic embryogenesis of banana - Adero, M.O.; Tripathi, J.; Tripathi, L. (MDPI, 2023)
The cultivation of bananas and plantains (Musa spp.) holds significant global economic importance, but faces numerous challenges, which may include diverse abiotic and biotic factors such as drought and various diseases caused by fungi, viruses, and bacteria. The genetic and asexual nature of cultivated banana cultivars makes them unattractive for improvement via traditional breeding. To overcome these constraints, modern biotechnological approaches like genetic modification and genome editing have become essential for banana improvement. However, these techniques rely on somatic embryogenesis, which has only been successfully achieved in a limited number of banana cultivars. Therefore, developing new strategies for improving somatic embryogenesis in banana is crucial. This review article focuses on advancements in banana somatic embryogenesis, highlighting the progress, the various stages of regeneration, cryopreservation techniques, and the molecular mechanisms underlying the process. Furthermore, this article discusses the factors that could influence somatic embryogenesis and explores the prospects for improving the process, especially in recalcitrant banana cultivars. By addressing these challenges and exploring potential solutions, researchers aim to unlock the full potential of somatic embryogenesis as a tool for banana improvement, ultimately benefiting the global banana industry.